Analysing the likely impact of the new Namibia Investment Promotion Act 9 of 2016 on the flow of FDI into the country - OluSoyeju, Olufemi Olugbemiga (University of Pretoria, 2018)
Mini Dissertation (LLM)--University of Pretoria, 2017.